Faktor Risiko yang Berhubungan dengan Skor Maternal-Fetal Attachment pada Ibu Hamil - Wahidah Sukriani; Endang Koni Suryaningsih (Politeknik Kesehatan Tanjung Karang, 2018)
Maternal-Fetal Attachment (MFA) is a bond between mother and fetus during pregnancy. MFA plays an important role in maternal and fetal health and affects mothers' decisions in healthy behaviors during pregnancy. Several factors predicted to affect the MFA is the age of pregnancy, maternal age, gravida, pregnancy status, marital status, occupation, income and education of the mother. This study aims to determine the factors associated with maternal-fetal attachment scores in pregnant women in the Panarung Puskesmas Palangka Raya. This was an observational analytic study with a cross-sectional design. A sample in this research is a pregnant woman who does a pregnancy examination at Puskesmas Panarung Kota Palangka Raya. The instrument used in this research is the Indonesian version of prenatal attachment inventory (IPAI). Data analysis was done by logistic regression. The results of statistical tests showed a significant relationship between gestational age with MFA score (p<0.05). Mothers with a gestational age >28 weeks had a better MFA score because the mother already felt the presence of her fetus.